Exploring theatrical conventions and the application of palimpsest, polyphony, hauntology, and site-specific, through a scenographic lens - Mizrachi, Daniella (Little Theatre, 2025)
This written explication serves as a frame to understand and generate a site-specific performance that is through a scenographic lens. Scenography as defined through The Cambridge Introduction to Scenography (McKinney & Butterworth, 2015), states that scenography is a vital part of performance. By focusing on the scenographic elements of space, time and scenic environment, an understating of site-specific performance can be constructed. These elements are vital in the comprehension of space, they create a language to understand how to intervene in a chosen site of performance. The question posed is how do we create in these spaces? What vocabulary and techniques are required to be able to intervene scenographically? By engaging with the concept of hauntology as defied by Nicholas Abraham and Maria Torok, where spectres of the past linger through generational trauma and must be acknowledged to move forward, scenographic intervention into site-specific spaces engages and creates alongside a spectre of the past. The visual and audible techniques of palimpsest and polyphony, aid in the scenographic construction of sitespecific intervention. Palimpsest, originally located in literature as a way to reuse books and paper, ink would stain the pages which would create a ghostly effect and signify the presence of the author. The visual application of palimpsest, of a ghostly trace is how a production visually might be structured, a presence in absence, signifying the past in the present. Polyphony although originating in music, is another way to layer and structure a language or soundtrack that accompanies a site-specific intervention. By engaging with polyphony as the complexity of sound and layering phrases of voices and music to create a polyphonic soundtrack to our spaces of performances or our heritage sites as performance spaces. By using the frame of hauntology as a way in which to confront and understand how these spaces can affect both performance and spectator, we acknowledge the past and work alongside it in the present. This practice-based explication serves as a guide to understanding and engaging with a site-specific work set within a heritage site.